Analisis Penerapan Akuntansi Pada Badan Usaha Milik Desa (Bumdes) Maduma Desa Palipi Kabupaten Samosir - Adelima Hutabaalian; Hendrik ES Samosir; Ardin Dolok Saribu (Jurnal Minfo Polgan, 2024)
The aim of this research was to find out whether BUMDes Maduma Palipi village had implemented generally accepted accounting principles. The types of data used in this research are primary data and secondary data. Primary data is data obtained from interviews with BUMDes administrators regarding the history of the establishment of BUMDes, the recording system implemented by BUMDes, accounting policies implemented by BUMDes and regarding BUMDes activities. Secondary data is data obtained by collecting data that has been compiled by BUMDes administrators, such as balance sheets and profit and loss.In analyzing the research data, the author used a descriptive method, namely data obtained from the company was then arranged in such a way and analyzed based on relevant theories and then conclusions were drawn.Based on the research results, it was found that the basis for recording was carried out using an accrual basis. BUMDes Maduma Palipi village has not yet implemented the accounting stages completely. BUMDes Maduma Palipi village only presents a balance sheet and profit and loss report. BUMDes Maduma Palipi village does not present capital change reports, cash flow reports or notes to financial reports. From the results of this research, researchers can conclude that the application of accounting at BUMDes Maduma Palipi village is not in accordance with generally accepted accounting principles.